Synthesis report on the co-design of agroecological innovations in the Agroecological Living Landscapes (ALLs) in Kenya - Fuchs, Lisa E.; Korir, Hezekiah; Bolo, Peter; Sakha, Michael; Gumo, Pius; Mbelwa, Machio; Kuria, Anne; Adoyo, Beatrice; Syano, Nicholas; Kiruthi, Esther; Baijukya, Frederick; Baudron, Frédéric (2024)
In Kenya, the CGIAR Agroecology Initiative (AE-I) has two agroecological living landscapes (ALLs), one in Kiambu County and a second in Makueni County. Work package 1 (WP1) of the AE-I entailed two key components: ALL establishment, and innovation co-design. In line with broader agroecology approaches and ontologies, both were to be achieved through transdisciplinary co-design processes. This report provides an overview of the innovation co-design process, its results, the scientific performance of co-designed practices and related reflections. First, the report introduces the three-pronged co-design approach, which included a preparatory phase, a co-design phase, and a trial phase; and outlines the many different steps involved in the process. It then provides details of the specific practices co-designed across the three identified focus areas in which most attention was required: soil management, water management, and integrated pest management. The respective practices for the Kiambu ALL included the use of compost manure, mulch, and chili-based biopesticides, and farmyard manure, planted terraces, and neem-based biopesticides in Makueni. In the first cycle of trials, each of these practices was put under trial on 10 farmers’ fields. The experimental design included on 5x6 m controlled test trial plot, and a second 5x6 m “uncontrolled” control plot. While the inputs used (including seeds, seedlings, and treatments) were centrally provided, and kept constant, the trial participants used their conventional practice in the control plots. With a few exceptions, this conventional practice is largely organic in Kiambu, and followed permaculture principles in Makueni. Third, the agronomic assessment of two consecutive experimentation cycles (October 2023-March 2024; May 2024-September 2024) revealed generally positive performance of the co-designed practices. A preliminary contextual climate analysis showed that both areas received excessive rainfall in the second cycle, with more than twice the long-term average in April and May. Experienced flooding and water logging considerably influenced agricultural production during that cycle. Considering gross productivity, yields only significantly improved in the Makueni ALL, while differences in Kiambu ALL were not significant. In Makueni, only farmyard manure had a significant effect on maize yields, while all three practices significantly improved bean yields. Considering pest and disease pressure, pests were significantly lower for cabbages in the IPM trials in Kiambu, but not for compost or mulch. In Makueni, pests were significantly lower for both maize and beans in the IPM trial, as well as for beans in the manure trial. Despite experiencing difficulties related to planting timing, the climatic conditions, the quality of the inputs used, and market constraints, the participating farmers evaluated the practices and their participation in the trials very positively. In the last two sections, the report discussed adoption and scaling approaches, and broader reflections on successes and challenges with the co-design process, and recommends a continuation of highly methodical and structured transdisciplinary innovation co-design. This report complements the detailed co-design report prepared by the WP1 Kenya team in 2023 (Fuchs et al., 2023b).